Do Search Engines Increase Concentration in Media Markets? - Joan Calzada; Nestor Duch-Brown; Ricard Gil (Center for Economic Studies and ifo Institute (CESifo), 2023)
Search engines are important access channels to news content of traditional newspapers with Google alone responsible for 35% of online visits to news outlets in the European Union. Yet, the effects of Google Search on market competition and information diversity have received scant attention. Using daily traffic data for 606 news outlets from 15 European countries, we analyze Google's capacity to influence organic search visits by exploiting exogenous variation in news outlets' indexation caused by nine core algorithm updates rolled out by Google between 2018 and 2020. We find Google core updates overall reduced the number of keywords (queries) for which news outlets occupy one of the top 10 organic search results positions. Therefore, given the positive impact that the number of top keywords have on traffic this led to the decrease in the overall number of news outlets' visits. Finally, when studying the impact of Google core updates on media market concentration, we find the three "big" core updates identified in this period reduced market concentration by 1%, but this effect was offset by the rest of the updates. Similarly, in the context of Spain, we find the three "big" core updates reduced monthly keyword concentration by 4%.
Keywords: D43; L50; L82; M31; 330; search engines; market concentration Google; news sites; Europe